Exploring the economic and noneconomic determinants of investments in renewable energy - Mohammed Gazi Salah Uddin; Md. Bokhtiar Hasan; Donghyun Park; Md. Sumon Ali; Christoffer Wadström (Asian Development Bank (ADB), 2024)
Amid a shifting global energy landscape driven by concerns about climate change and fossil fuel depletion, there is a heightened need to move toward sustainable energy sources. Although there has been a significant increase in investments in renewable energy (RE) globally, there is still a considerable shortfall in achieving sustainability goals. This study is the first to explore the determinants of RE investments, considering a range of important economic and noneconomic variables. The research employs a balanced annual panel dataset covering 36 countries from 2000 to 2020. The findings indicate that, in developed economies, industrial growth, environmental taxes, social globalization, and climate vulnerability positively influence RE investments, while inflation and political instability have negative impacts. In developing economies, environmental taxes, social globalization, environmental technologies, and climate vulnerability are beneficial, while industrial growth and oil prices have adverse effects. These factors are significant for policy, providing governments and policymakers with valuable information to create specific strategies to meet global sustainability goals.
Keywords: C33; F64; Q50; Q42; 330; renewable energy investments; economic and noneconomic factors; developed and developing economies; panel data estimates